2011
DOI: 10.1210/en.2010-1116
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Programming of Gene Expression in Growth-Restricted Rats Depends on the Cause of Low Birth Weight

Abstract: Low birth weight and intrauterine growth restriction (IUGR) can be caused by numerous different conditions. In many experimental settings, however, these different causes are not accounted for. This study aimed at comparing the impact of two frequent causes of IUGR (low utero-placental blood flow vs. malnutrition) on fetal programming of gene expression. We studied offspring of dams treated by uterine artery ligation or sham operation compared with untreated controls and offspring of dams that were fed either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 39 publications
1
35
1
Order By: Relevance
“…In the present study, dams had adapted their metabolism to the diet before entering pregnancy, and that may explain the fact that, although the expression of the growth-promoting genes was reduced in the R group, the pups did not suffer from intrauterine growth restriction (IUGR) [52]. It is indeed now established that maternal nutrition may have long-lasting consequences on offspring metabolic outcomes without any impact on birth weight, both in humans [78] and animal models [12,79–80], and these consequences rely more on the time-window and nature of the nutritional insult than on growth restriction per se [80]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, dams had adapted their metabolism to the diet before entering pregnancy, and that may explain the fact that, although the expression of the growth-promoting genes was reduced in the R group, the pups did not suffer from intrauterine growth restriction (IUGR) [52]. It is indeed now established that maternal nutrition may have long-lasting consequences on offspring metabolic outcomes without any impact on birth weight, both in humans [78] and animal models [12,79–80], and these consequences rely more on the time-window and nature of the nutritional insult than on growth restriction per se [80]. …”
Section: Discussionmentioning
confidence: 99%
“…A series of epidemiological studies have demonstrated that poor growth in utero is associated with increased risk of developing obesity and other MetS (14,15). Experimentally, a number of animal models resorting to maternal malnutrition during pregnancy (16,17), fetal exposure to elevated glucocorticoid levels (18,19), or surgical ligation of the uterine arteries (20) have been used. It has been reported that uteroplacental insufficiency in rats caused impaired glucose tolerance, hyperinsulinemia as well as elevated plasma triglycerides and leptin levels in adult offspring (21).…”
mentioning
confidence: 99%
“…Following veterinarian judgment, buprenorphine hydrochloride was injected when pain or discomfort was imminent. Our animal model was previously described in detail [8], [22]. Virgin female Wistar rats were obtained from Charles River Laboratories International, Inc. (Sulzfeld, Germany) and housed at the University's animal facility.…”
Section: Methodsmentioning
confidence: 99%
“…The pregnant dams were then randomized into two dietary groups, normal and low protein (casein) (NP and LP respectively). Throughout pregnancy animals were fed a semi-purified diet, as previously described [22]: NP rats (n = 8) received 25 g/d of Altromin C1000 containing 17.0% protein, while LP animals (n = 8) were fed 25 g/d of Altromin C1003 containing 8.8% protein. Diets were isocaloric.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation